A gel system self-healing anti-corrosion coating and its preparation method and application
By combining polysaccharide gels with carbon nanotubes in oil and gas fields, an anticorrosion coating that can heal is prepared by solving the problem of existing coatings in such high sulfur, high oil and high temperature environments. The applicability issues in the environment have achieved the improvement of the self-healing and corrosion resistance of the coating.
Patent Information
- Application Number
- CN202210353931.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-04-06
AI Technical Summary
The existing self-healing coatings are not suitable for highly corrosive environments such as oil and gas fields with high sulfur content, high oil content and high temperature.
A polysaccharide gel is used as the basis and carbon nanotubes are added to prepare a self-healing anticorrosion coating with self-healing ability. This coating is prepared by cross-linking reaction between polysaccharides and cross-linking agents, and cross-linking is carried out in the presence of a modifier to form a modified polysaccharide-based gel, combining the repair ability of carbon nanotubes to achieve self-healing in a high-temperature environment Combined effect.
This coating not only shows good corrosion resistance in high temperature environments, but also has self-healing ability, can automatically repair damage and extend service life. It is suitable for pipelines and equipment surfaces in strong corrosion environments such as oil and gas fields.
Smart Images

Figure BDA0003582004620000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a gel system self-healing anti-corrosion coating and a preparation method and application thereof. Background Art
[0002] In the process of oil and natural gas extraction, the temperature of the extracted crude oil and natural gas out of the well is often high, usually above 90°C, and contains a large amount of corrosive substances, such as hydrogen sulfide gas, microorganisms, etc., which cause serious corrosion to the transmission pipelines and equipment, affecting their service life. Therefore, the pipelines and equipment at the oil and gas well extraction sites need to be made of high-temperature anti-corrosion materials, and need to be coated with high-temperature anti-corrosion materials on the surface for protection to extend their service life. Due to the serious corrosion in the development environment of oil and gas fields, the anti-corrosion coatings coated on the surface of pipelines and equipment will corrode after a period of time and gradually deteriorate. Therefore, in order to ensure production safety, regular shutdowns for maintenance and re-coating will be carried out to avoid safety hazards. However, re-shutdowns for maintenance and re-coating will affect the output of oil and gas fields and increase the production costs of oil and gas fields.
[0003] Patent 201710267407.4 reports a method for preparing a self-healing antibacterial coating, and discloses the application of the prepared self-healing antibacterial coating loaded with antibacterial drugs and / or bioactive antibacterial peptides in the field of biomedical materials.
[0004] Patent 201910980198.7 reports a self-healing anti-corrosion and anti-fouling integrated coating material, its preparation method and application. The coating material includes a styrene-based thermoplastic elastomer and a solvent; the solvent is a lubricating liquid with low surface energy and a high boiling point, and is also a poor solvent for the hard segments and a good solvent for the soft segments in the styrene-based thermoplastic elastomer. At room temperature, the styrene segments aggregate and, as physical crosslinking points, form a physical crosslinking network with other blocks to form a physical oil gel with reversible crosslinking ability; its reversible physical crosslinking process enables it to achieve a reversible crosslinking process before and after the gelation temperature, giving the gel self-healing ability under light / heat stimulation. An anti-corrosion and anti-fouling integrated coating material with self-healing properties is constructed through a reversible gelation process of "high temperature dissolution-low temperature gelation", but the "high temperature dissolution" characteristic makes it impossible to use it in a high temperature environment.
[0005] Although the self-healing coating disclosed in the prior art can achieve the self-healing effect, there is no report on the self-healing coating in the environment of high sulfur content, high oil content and high temperature such as oil and gas fields. Summary of the invention
[0006] In order to solve the problem that the existing self-healing coating is not suitable for highly corrosive environments with high sulfur content, high oil content and high temperature such as oil and gas fields. The present invention provides a gel system self-healing anti-corrosion coating. The present invention also provides a preparation method of the gel system self-healing anti-corrosion coating. The present invention also provides an application of the gel system self-healing anti-corrosion coating.
[0007] The technical solution of the present invention:
[0008] According to the first technical solution of the present invention, a gel system self-healing anti-corrosion coating includes 15-25% self-healing gel, 0.5-1.5% carbon nanotubes, and the remainder is solvent water; the self-healing gel is a polysaccharide-based gel.
[0009] According to the second technical scheme of the present invention, a method for preparing a gel system self-healing anti-corrosion coating comprises the following steps: S1) preparing a polysaccharide-based gel by cross-linking a polysaccharide with a cross-linking agent; S2) dissolving the polysaccharide-based gel in solvent water, and then adding carbon nanotubes in proportion, and dispersing them evenly to obtain a gel system self-healing anti-corrosion coating.
[0010] The preparation of the polysaccharide-based gel in step S1) comprises the following steps: mixing a polysaccharide aqueous solution with an initiator aqueous solution, stirring evenly to obtain a reaction solution, adding a crosslinker aqueous solution to the reaction solution, stirring evenly, and heating to cause a crosslinking reaction to obtain the polysaccharide-based gel.
[0011] The polysaccharide is one or more of chitosan, heparin and hydroxypropyl cellulose, the cross-linking agent is diallyl disulfide or N,N-methylenebisacrylamide, and the initiator is cerium ammonium nitrate.
[0012] During cross-linking, the heating temperature is 45-70° C., and the reaction time is 4-16 hours.
[0013] The stirring time when the polysaccharide solution and the initiator are mixed is 30 to 90 minutes, and the stirring speed is 1000 to 4000 r / min.
[0014] When the initiator and the polysaccharide solution are mixed, an acid is added to adjust the pH value to 2-4, and the acid is any one of nitric acid, hydrochloric acid or hydrofluoric acid.
[0015] According to the third technical solution of the present invention, a gel system self-healing anti-corrosion coating includes 15-25% self-healing gel, 0.5-1.5% carbon nanotubes, and the remainder is solvent water, measured by mass fraction; the self-healing gel is a modified polysaccharide-based gel.
[0016] According to the fourth technical scheme of the present invention, the method for preparing a gel system self-healing anti-corrosion coating comprises the following steps: S1) preparing a modified polysaccharide-based gel by cross-linking a polysaccharide and a cross-linking agent in the presence of a modifier; S2) dissolving the modified polysaccharide-based gel in solvent water, and then adding carbon nanotubes in proportion, and dispersing them evenly to obtain a gel system self-healing anti-corrosion coating.
[0017] The preparation of the modified polysaccharide-based gel in step S1) comprises the following steps: mixing a polysaccharide solution with an initiator solution, stirring them evenly to obtain a reaction solution, adding a modifier to the reaction solution, stirring and mixing them evenly, and heating them to obtain a modified reaction solution, adding a crosslinker solution to the modified reaction solution, stirring, and heating them to cause a crosslinking reaction to obtain the modified polysaccharide-based gel.
[0018] The polysaccharide is one or more of chitosan, heparin and hydroxypropyl cellulose, the crosslinking agent is diallyl disulfide or N,N-methylenebisacrylamide, the initiator is ammonium cerium nitrate, and the modifier is at least one of silicone or polyether.
[0019] The stirring time when the polysaccharide solution and the initiator are mixed is 30 to 90 minutes, and the stirring speed is 1000 to 4000 r / min.
[0020] The heating temperature for preparing the modified reaction solution is 35-60°C, and the reaction time is 8-12h.
[0021] The heating temperature during the cross-linking reaction is 45 to 70° C., and the reaction time is 4 to 16 hours.
[0022] When the initiator and the polysaccharide solution are mixed, an acid is added to adjust the pH value to 2-4, and the acid is any one of nitric acid, hydrochloric acid or hydrofluoric acid.
[0023] The application of a gel system self-healing anti-corrosion coating described in the first and third technical solutions of the present invention is used to coat the surface of pipelines and equipment in the highly corrosive environment of high sulfur content, high oil content and high temperature in oil fields as a self-healing anti-corrosion coating.
[0024] Beneficial technical effects of the present invention:
[0025] The present invention provides a gel system self-healing coating, which is prepared into a coating with self-healing ability by using a polysaccharide-based gel with a reversible characteristic group and adding carbon nanotubes with repair ability. The coating has a certain healing ability for coating damage and a long service life. At the same time, the polysaccharide-based gel of the present invention is prepared by cross-linking a polysaccharide with a cross-linking agent. Since the polysaccharide itself has corrosion resistance, the polysaccharide-based gel obtained by cross-linking with the cross-linking agent has good corrosion resistance and self-assembly force. Due to the ratio of the two, the carbon nanotubes and the polysaccharide-based gel are easy to form a stable nano system, so that the carbon nanotubes are evenly distributed and the coating is stable, which improves the corrosion resistance of the coating, so that the self-healing anti-corrosion coating not only has good corrosion resistance, but also automatically repairs damage and prolongs the service life. It is suitable for anti-corrosion coatings coated on the surface of pipelines and equipment in highly corrosive environments with high sulfur content, high oil content and high temperature such as oil and gas fields, without stopping production for maintenance.
[0026] Preferably, the polysaccharide-based gel is replaced with a modified polysaccharide-based gel. Under the modification in silicone or polyether, the number of active groups (such as hydroxyl groups) is reduced, the stability of the polysaccharide-based gel is better, and the resistance to strong corrosive environments is improved.
[0027] In the preparation method of the present invention, firstly, a polysaccharide-based gel is prepared by cross-linking a polysaccharide with a cross-linking agent, or a modified polysaccharide-based gel is prepared by cross-linking a polysaccharide with a cross-linking agent in the presence of a modifier, and then the polysaccharide-based gel or the modified polysaccharide-based gel is dissolved in solvent water, and then carbon nanotubes are added according to a proportion, and after uniform dispersion, a gel system self-healing anti-corrosion coating is obtained. The preparation method is simple and the raw materials are environmentally friendly.
[0028] Preferably, the preparation of the polysaccharide-based gel by cross-linking polysaccharides with cross-linking agents comprises the following steps: mixing a polysaccharide aqueous solution with an initiator aqueous solution, controlling the stirring time to be 30 to 90 minutes and the stirring rate to be 1000 to 4000 r / min, thereby stirring evenly to obtain a reaction solution; adding a cross-linking agent aqueous solution to the reaction solution, stirring evenly, heating, controlling the temperature to be 45 to 70° C., and reacting for 4 to 16 hours to allow chemical cross-linking to occur, thereby obtaining a stable polysaccharide-based gel.
[0029] Preferably, the preparation of the modified polysaccharide-based gel by cross-linking polysaccharides and cross-linking agents in the presence of a modifier comprises the following steps: mixing a polysaccharide solution with an initiator solution, controlling the stirring time to be 30 to 90 minutes and the stirring rate to be 1000 to 4000 r / min, thereby stirring evenly to obtain a reaction solution, adding a modifier to the reaction solution, stirring and mixing evenly, controlling the heating temperature to be 35 to 60° C. and the reaction time to be 8 to 12 hours to obtain a modified reaction solution, which helps the modifier to combine with the polysaccharide and allows the subsequent cross-linking reaction to occur stably, then adding a cross-linking agent solution to the modified reaction solution, stirring, and heating, controlling the temperature to be 45 to 70° C. and the reaction time to be 4 to 16 hours, chemical cross-linking to occur, and obtaining a more stable modified polysaccharide-based gel.
[0030] Preferably, the polysaccharide is one or more of chitosan, heparin and hydroxypropyl cellulose, the crosslinking agent is diallyl disulfide or N,N-methylenebisacrylamide, and the initiator is ammonium cerium nitrate, thereby forming a polysaccharide-based gel and a modified polysaccharide-based gel having reversible characteristic groups.
[0031] Preferably, when the initiator and the polysaccharide solution are mixed, an acid is added to adjust the pH value to 2-4 so that the cross-linking reaction occurs stably, and the acid is any one of nitric acid, hydrochloric acid or hydrofluoric acid.
[0032] Preferably, the concentration of the polysaccharide solution is 10%-15%, the concentration of the crosslinking agent solution is 0.5%-0.7%, and the concentration of the initiator solution is 0.5%-0.7%, so that the crosslinking reaction occurs stably. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Example 1
[0035] A gel system self-healing anti-corrosion coating comprises 15% self-healing gel, 0.5% carbon nanotubes (manufacturer: Sinopharm, aspect ratio of 10-100) by mass fraction, and the remainder is solvent water. The self-healing gel is a polysaccharide-based gel.
[0036] The preparation method of the above-mentioned gel system self-healing anti-corrosion coating uses carbon nanotubes, chitosan, diallyl disulfide, ammonium cerium nitrate and water as raw materials, and comprises the following steps:
[0037] S1) preparing a polysaccharide-based gel by cross-linking polysaccharides with a cross-linking agent
[0038] S111) dissolving chitosan in water to obtain a polysaccharide solution with a mass fraction of 10%; dissolving an initiator, ammonium cerium nitrate, in water to prepare an initiator solution with a mass fraction of 0.5%; dissolving a crosslinking agent, diallyl disulfide, in water to prepare a crosslinking agent solution with a mass fraction of 0.5%, for later use;
[0039] S112) adding the polysaccharide solution to the initiator solution, adding nitric acid to adjust the pH value to 3 under stirring, and then continuing to stir at a stirring speed of 4000 r / min for 30 min to obtain a reaction solution;
[0040] S113) adding a crosslinking agent solution to the reaction solution, stirring and mixing evenly, and heating to 45° C., reacting for 16 hours to obtain a polysaccharide-based gel.
[0041] S2) The prepared polysaccharide-based gel is dissolved in water to obtain a self-healing gel solution with a mass fraction of 15%, and then 0.5% of carbon nanotubes are added and dispersed evenly to obtain coating A.
[0042] Example 2
[0043] A gel system self-healing anti-corrosion coating comprises 25% self-healing gel, 1.5% carbon nanotubes (manufacturer: Sinopharm, aspect ratio of 10-100) by mass fraction, and the remainder is solvent water. The self-healing gel is a polysaccharide-based gel.
[0044] The preparation method of the above-mentioned gel system self-healing anti-corrosion coating uses carbon nanotubes, ammonium cerium nitrate, chitosan, diallyl disulfide and water as raw materials, and comprises the following steps:
[0045] S1) preparing a polysaccharide-based gel by cross-linking polysaccharides with a cross-linking agent
[0046] S111) dissolving chitosan in water to obtain a polysaccharide solution with a mass fraction of 15%; dissolving an initiator, ammonium cerium nitrate, in water to prepare an initiator solution with a mass fraction of 0.7%; dissolving a crosslinking agent, diallyl disulfide, in water to prepare a crosslinking agent solution with a mass fraction of 0.7% for later use;
[0047] S112) adding the polysaccharide solution to the initiator solution, stirring and adding nitric acid to adjust the pH value to 3, and then continuing to stir at a stirring speed of 1000 r / min for 90 min to obtain a reaction solution;
[0048] S113) adding a crosslinking agent solution to the reaction solution, stirring and mixing evenly, and heating to 70° C. and reacting for 4 hours to obtain a polysaccharide-based gel.
[0049] S2) The prepared polysaccharide-based gel is dissolved in water to obtain a self-healing gel solution with a mass fraction of 25%, and then 1.5% of carbon nanotubes are added and dispersed evenly to obtain coating B.
[0050] Example 3
[0051] A gel system self-healing anti-corrosion coating comprises 20% self-healing gel, 0.8% carbon nanotubes (manufacturer: Sinopharm, aspect ratio of 10-100) by mass fraction, and the remainder is solvent water. The self-healing gel is a polysaccharide-based gel.
[0052] The preparation method of the above-mentioned gel system self-healing anti-corrosion coating uses carbon nanotubes, ammonium cerium nitrate, chitosan, diallyl disulfide and water as raw materials, and comprises the following steps:
[0053] S1) preparing a polysaccharide-based gel by cross-linking polysaccharides with a cross-linking agent
[0054] S111) dissolving chitosan in water to obtain a polysaccharide solution with a mass fraction of 12%; dissolving an initiator, ammonium cerium nitrate, in water to prepare an initiator solution with a mass fraction of 0.5%; dissolving a crosslinking agent, diallyl disulfide, in water to prepare a crosslinking agent solution with a mass fraction of 0.5% for later use;
[0055] S112) adding the polysaccharide solution to the initiator solution, stirring and adding nitric acid to adjust the pH value to 3, and then continuing to stir at a stirring speed of 2000 r / min for 60 min to obtain a reaction solution;
[0056] S113) adding a crosslinking agent solution to the reaction solution, stirring and mixing evenly, and heating to 50° C. and reacting for 8 hours to obtain a polysaccharide-based gel.
[0057] S2) The prepared polysaccharide-based gel is dissolved in water to obtain a self-healing gel solution with a mass fraction of 20%, and then 0.8% of carbon nanotubes are added and dispersed evenly to obtain a coating C.
[0058] Example 4
[0059] A gel system self-healing anti-corrosion coating comprises 20% self-healing gel, 0.8% carbon nanotubes (manufacturer: Sinopharm, aspect ratio of 10-100) by mass fraction, and the remainder is solvent water. The self-healing gel is a modified polysaccharide-based gel.
[0060] The preparation method of the above-mentioned gel system self-healing anti-corrosion coating uses carbon nanotubes, ammonium cerium nitrate, organic siloxane, chitosan, diallyl disulfide and water as raw materials, and comprises the following steps:
[0061] S1) preparing a modified polysaccharide-based gel by cross-linking a polysaccharide with a cross-linking agent in the presence of a modifier
[0062] S121) dissolving chitosan in water to obtain a polysaccharide solution with a mass fraction of 10%; dissolving ammonium cerium nitrate in water to prepare an initiator solution with a mass fraction of 0.5%; dissolving diallyl disulfide in water to prepare a cross-linking agent solution with a mass fraction of 0.5%, which is used for standby;
[0063] S122) adding the polysaccharide solution to the initiator solution, adding nitric acid to adjust the pH value to 3 under stirring, and then continuing to stir at a stirring speed of 4000 r / min for 30 min to obtain a reaction solution;
[0064] S123) adding 5% by mass of a siloxane modifier to the reaction solution, stirring and mixing evenly, heating to 35° C., and reacting for 12 h to obtain a modified reaction solution;
[0065] S124) adding a crosslinking agent solution to the modified reaction solution, stirring and mixing evenly, and heating to 50° C. and reacting for 8 hours to obtain a modified polysaccharide-based gel.
[0066] S2) dissolving the prepared modified polysaccharide-based gel in water to obtain a self-healing gel solution with a mass fraction of 20%, and then adding 0.8% of carbon nanotubes with a mass fraction, and after uniform dispersion, a coating D can be obtained.
[0067] Example 5
[0068] A gel system self-healing anti-corrosion coating comprises 20% self-healing gel, 0.8% carbon nanotubes (manufacturer: Sinopharm, aspect ratio of 10-100) by mass fraction, and the remainder is solvent water. The self-healing gel is a modified polysaccharide-based gel.
[0069] The preparation method of the above-mentioned gel system self-healing anti-corrosion coating uses carbon nanotubes, ammonium cerium nitrate, organic siloxane, chitosan, diallyl disulfide and water as raw materials, and comprises the following steps:
[0070] S1) preparing a modified polysaccharide-based gel by cross-linking a polysaccharide with a cross-linking agent in the presence of a modifier
[0071] S121) dissolving chitosan in water to obtain a polysaccharide solution with a mass fraction of 12%; dissolving ammonium cerium nitrate in water to prepare an initiator solution with a mass fraction of 0.5%; dissolving diallyl disulfide in water to prepare a cross-linking agent solution with a mass fraction of 0.5%, which is used for standby;
[0072] S122) adding the polysaccharide solution to the initiator solution, stirring and adding nitric acid to adjust the pH value to 3, and then continuing to stir at a stirring speed of 2000 r / min for 60 min to obtain a reaction solution;
[0073] S123) adding 5% by mass of a siloxane modifier to the reaction solution, stirring and mixing evenly, and heating to 40° C. to react for 8 h to obtain a modified reaction solution;
[0074] S124) adding a crosslinking agent solution to the modified reaction solution, stirring and mixing evenly, and heating to 50° C. to perform a crosslinking reaction for 8 hours to obtain a modified polysaccharide-based gel.
[0075] S2) dissolving the prepared modified polysaccharide-based gel in water to obtain a self-healing gel solution with a mass fraction of 20%, and then adding 0.8% of carbon nanotubes with a mass fraction, and after uniform dispersion, a coating E can be obtained.
[0076] Self-healing performance test
[0077] The coatings AE prepared above were coated on metal plates respectively, and after film formation, a coating with a thickness of 0.5 mm was formed, and a sharp object was used to slide a scratch with a length of 2 cm on each coating, and then the metal plate was heated to 50°C, and the coating repair efficiency was tested by electrochemical AC impedance spectroscopy. The results are shown in Table 1. For crack-type damage, it can heal itself, but it is relatively slow. Preferably, heating or charging can accelerate the healing rate, and it can heal itself within 3 to 5 hours.
[0078] Coatings AE were applied on metal plates respectively so that the metal plates were completely covered by the coatings. After they dried naturally, a coating with a thickness of 0.5 mm was formed. The metal plates coated with the coatings were placed in a liquid with a hydrogen sulfide content of 0.6% and an oil content of 1578 mg / L. The liquid was left to stand for 360 days and its corrosion was observed. The test results are shown in Table 1.
[0079] Coatings AE were applied on metal plates respectively so that the metal plates were completely covered by the coatings. After they dried naturally, a coating with a thickness of 0.5 mm was formed. The metal plates coated with the coatings were placed in a liquid with a hydrogen sulfide content of 0.6% and an oil content of 1578 mg / L. The liquid was kept at a constant temperature of 90°C for 60 days to observe the corrosion. The test results are shown in Table 1.
[0080] Table 1. Coating repair effects of Examples 1-5
[0081]
[0082] It can be seen that the gel system self-healing anti-corrosion coating disclosed in Examples 1-5 of the present invention not only has good corrosion resistance in highly corrosive environments with high sulfur content, high oil content and high temperature such as oil and gas fields, but also has good self-healing effect on coating damage and has a long service life.
[0083] The representative embodiments and test examples of the present invention are described in detail above, but the present invention is not limited to the specific details in the above-mentioned embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical scheme of the present invention. Changes and combinations that are obvious to those skilled in the art all fall within the scope of protection of the present invention.
Claims
1. A gel system self-healing anti-corrosion coating, characterized in that The invention comprises 15-25% self-healing gel and 0.5-1.5% carbon nanotubes by mass fraction, and the remainder is solvent water; the self-healing gel is a polysaccharide-based gel, and the preparation of the polysaccharide-based gel comprises the following steps: mixing a polysaccharide aqueous solution with an initiator aqueous solution, stirring evenly to obtain a reaction solution, adding a crosslinker aqueous solution to the reaction solution, stirring evenly, and heating to generate a crosslinking reaction to obtain the polysaccharide-based gel, wherein the polysaccharide is one or more of chitin, heparin and hydroxypropyl cellulose, the crosslinker is diallyl disulfide or N,N'-methylenebisacrylamide, and the initiator is ammonium cerium nitrate.
2. The method for preparing a gel system self-healing anti-corrosion coating according to claim 1, characterized in that The following steps are involved: S1) preparing a polysaccharide-based gel by cross-linking a polysaccharide with a cross-linking agent; S2) dissolving the polysaccharide-based gel in solvent water, then adding carbon nanotubes according to a proportion, and obtaining a gel system self-healing anti-corrosion coating after uniform dispersion.
3. The method according to claim 2, characterized in that During cross-linking, the heating temperature is 45-70° C., and the reaction time is 4-16 hours.
4. The method according to claim 2, characterized in that The stirring time when the polysaccharide aqueous solution and the initiator aqueous solution are mixed is 30 to 90 minutes, and the stirring speed is 1000 to 4000 r / min.
5. The method according to claim 2, characterized in that When the initiator aqueous solution and the polysaccharide aqueous solution are mixed, an acid is added to adjust the pH value to 2-4, and the acid is any one of nitric acid, hydrochloric acid or hydrofluoric acid.
6. A gel system self-healing anti-corrosion coating, characterized in that The invention comprises 15-25% self-healing gel and 0.5-1.5% carbon nanotubes by mass fraction, and the remainder is solvent water; the self-healing gel is a modified polysaccharide-based gel, and the preparation of the modified polysaccharide-based gel comprises the following steps: mixing a polysaccharide solution with an initiator solution, stirring evenly to obtain a reaction solution, adding a modifier to the reaction solution, stirring and mixing evenly, and heating to obtain a modified reaction solution, adding a crosslinker solution to the modified reaction solution, stirring, and heating to generate a crosslinking reaction to obtain the modified polysaccharide-based gel, wherein the polysaccharide is one or more of chitosan, heparin and hydroxypropyl cellulose, the crosslinker is diallyl disulfide or N,N'-methylenebisacrylamide, the initiator is ammonium cerium nitrate, and the modifier is at least one of a silicone or a polyether.
7. The method for preparing a gel system self-healing anti-corrosion coating according to claim 6, characterized in that The following steps are involved: S1) preparing a modified polysaccharide-based gel by cross-linking a polysaccharide with a cross-linking agent in the presence of a modifier; S2) dissolving the modified polysaccharide-based gel in solvent water, then adding carbon nanotubes according to a proportion, and obtaining a gel system self-healing anti-corrosion coating after uniform dispersion.
8. The preparation method according to claim 7, characterized in that The stirring time when the polysaccharide solution and the initiator are mixed is 30 to 90 minutes, and the stirring speed is 1000 to 4000 r / min.
9. The preparation method according to claim 7, characterized in that The heating temperature for preparing the modified reaction solution is 35-60°C, and the reaction time is 8-12h.
10. The preparation method according to claim 7, characterized in that The heating temperature during the cross-linking reaction is 45 to 70° C., and the reaction time is 4 to 16 hours.
11. The method according to claim 7, characterized in that When the initiator and the polysaccharide solution are mixed, an acid is added to adjust the pH value to 2-4, and the acid is any one of nitric acid, hydrochloric acid or hydrofluoric acid.
12. Application of a gel system self-healing anti-corrosion coating according to claim 1 or 6, characterized in that Used as a self-healing anti-corrosion coating to coat the surfaces of pipelines and equipment in the highly corrosive environment of high sulfur, high oil content and high temperature in oil fields.
Citation Information
Patent Citations
A self-healing antibacterial coating, its preparation method and application
CN107216450B
A self-healing, corrosion-resistant, and anti-fouling integrated coating material, its preparation method, and its application.
CN110903730B
Method for preparing carbon nano tube / siliceous hybridized gel
CN101603041A
Carbon nano tube-carbon aerogel composite material and preparation method thereof
CN107056318A